Successful production of potato seed in Gujarat - Somani, Ashok K; Patel, Ashok; Thomas, George (Indian Horticulture, 2019)
Gujarat is the highest productive state for potato production in India and a flourishing market for processing varieties of potatoes. This skew towards processing varieties has meant that potato prices are relatively less fluctuating as compared to geographies where ware potato crop dominates. There have been periodic attempts in the past to start potato seed production by private/public sector players in Gujarat, but these remained unsuccessful till date, for some or the other reasons. Utkal Tubers India Pvt. Ltd. Bengaluru (UTIPL), collaborated with Sardarkrushinagar Dantiwada Agricultural University, Dantiwada (SDAU) and successfully produced potato seed in Deesa region (Banaskantha District) of Gujarat during autumn 2017-18.